Requirement of Digestible Methionine + Cystine to Molted Laying Hens - Oliveira Filho,PA (2019)
ABSTRACT The present study aimed to determine the ideal requirement of digestible methionine + cystine to molted laying hens. The experimental period lasted 105 days, divided into five periods of 21 days. 144 Hisex White laying hens with 84 weeks-of-age were used. The experimental design was completely randomized with treatments constituted for six levels of digestible methionine + cystine (0.45, 0.50, 0.55, 0.60, 0.65, and 0.70%) in the diets, with four replicates of six birds each. Data collected were evaluated by polynomial regression at 5%. There was a significant effect (p<0.05) of digestible methionine + cystine on feed intake, energy intake, protein intake, egg production, and egg mass. Internal egg quality presented positive linear effect (p<0.05) on albumen height and yolk color. External egg quality was affected (p<0.05) in eggshell %, eggshell thickness and eggshell resistance, where the level of 0.60% of digestible methionine + cystine in the diets provided eggshells with better quality (higher percentage, thicker and breaking resistance). Differences (p<0.05) were also observed in glucose and triglycerides concentration, with 0.60% of digestible methionine + cystine in the diets presenting better equilibrium. Results of the present study suggested that higher levels of digestible methionine + cystine improved the performance and internal egg quality of molted laying hens. The level of 0.60% of digestible methionine + cystine provided better eggshell and equilibrium on blood biochemistry.